Handbook of textile fibre structure. Volume 1, - Eichhorn, S. J. (Woodhead publishing in textiles, 2009)
Due to their complexity and diversity, understanding the structure of textile fibres is of key importance. This authoritative two-volume collection provides a comprehensive review of the structure of an extensive range of textile fibres.Volume 1 begins with an introductory set of chapters on fibre structure and methods to characterise fibres. The second part of the book covers the structure of manufactured polymer fibres such as polyester, polyamides, polyolefin, elastomeric and aramid fibres as well as high-modulus, high-tenacity polymer fibres. Chapters discuss fibre formation during.